2000
DOI: 10.1603/0022-2585-37.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Proboscis Amputation Facilitates the Study of Mosquito (Diptera: Culicidae) Attractants, Repellents, and Host Preference

Abstract: Proboscis amputation has facilitated the study of mosquito behavior. Using humans as a host is very important in the study of mosquito attractants, repellents, and host preference. However, mosquito bites cause potential medical problems because of hypersensitivity and perhaps secondary bacterial infection, even using laboratory mosquitoes. Moreover, once a normal female mosquito bites and feeds on human blood, it cannot be used in subsequent probing tests. These problems were resolved by proboscis amputation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…This procedure prior to release was recommended by the institutional ethics committee to avoid the risk of increased virus transmission in the dengue endemic area. Available evidence suggests that proboscis amputation should not affect postfeeding dispersal for oviposition (Shirai et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…This procedure prior to release was recommended by the institutional ethics committee to avoid the risk of increased virus transmission in the dengue endemic area. Available evidence suggests that proboscis amputation should not affect postfeeding dispersal for oviposition (Shirai et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Smith et al (1970) showed that the effectiveness of L-LA declined at high concentrations. We have described a new experimental method of assessing the response of Aedes albopictus (Skuse) to repellents (Shirai et al 2000) and herein compare our results with those reported previously.…”
mentioning
confidence: 52%
“…We adapted an aquarium (600 by 295 by 360 mm; NS-6 M, NISSO, Tokyo, Japan) as a test chamber and introduced mosquitoes into it after amputating their proboscises (Shirai et al 2000). L-LA (Wako Pure Chemical, Osaka, Japan) was diluted to concentrations ranging from 1 to 10,000 ppm with distilled water.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus ABO influences serum cholesterol level (Mayo et al 1969 and many subsequent studies) but the mechanism for this small effect is unknown. The same comment applies to the attraction for mosquitoes of some ABO phenotypes over others (Shirai et al 2000). Allen et al (2010) have shown, through a meta-analysis and other studies of over 2,800,000 single nucleotide polymorphisms in over 180,000 individuals, that genetic variants in over 180 gene loci influence human height.…”
Section: Polymorphism and Quantitative Variationmentioning
confidence: 96%